Self-regulated learning and personality in university students - Cepeda, Danna (2022)
The present investigation analyzes the relationship between the self-regulation of learning and the personality characteristics of university students belonging to the Minuto de Dios University Corporation - UNIMINUTO of Bogotá - Colombia the sample consisted of 75 men and women between 18 and 45 years of age. From the application of the instruments: Gordon's personality profile and inventory (ancestry, responsibility, emotional stability, sociability, caution, originality, commitment, vitality, and self-esteem) and the self-report questionnaire - self-regulation of learning, the correlational analysis was carried out. Using Spearman's Rho (significance level p<0.05). The results suggest that students who know and apply learning self-regulation techniques tend to be dominant (ancestry) independent, so they take responsibility for their personal goals (commitment), emotionally stable, and friendly. On the other hand, students who are cautious, original, and oriented towards understanding others tend to give little importance or use, to a lesser extent, the use of self-regulated learning strategies.